Perlindungan Hukum Bagi Para Pihak Atas Terjadinya Wanprestasi Dalam Transaksi Jual Beli Tanah - Mukiri, Steven; Handayati, Nur; Pramesti, Wahyu (Pusat Riset dan Inovasi Nasional, 2026)
In this thesis, the researcher intends to find out the Default in the case of Default in the Sale and Purchase of Land. In this case, the buyer feels disadvantaged by the Seller who has committed an act in the case of default. This study uses a Sale and Purchase Agreement between the Seller and the Buyer with the object of Residential Land. The seller in this case is in the position of Land Owner. (developer). And the buyer in this case is in the position of buyer in the sale and purchase of the land. This study uses a normative juridical method, namely research using a case approach accompanied by the Law. There are three forms of default, namely carrying out what has been agreed, but not as agreed and carrying out what has been agreed, but late in carrying out something that according to the agreement should not be carried out. So in the case of the case entering into one form of default, namely carrying out what has been agreed but not as agreed. The occurrence of a non-compliance with the agreement between the seller and the buyer, namely in the land sale and purchase agreement, in which the initial agreement stated the land area was 20,000M2. If the certificate is broken, the land area exceeds what was agreed upon, the buyer is obliged to pay Rp. 5,000,000 to the buyer.